ANALISIS PERBANDINGAN TRANSFORMASIONAL LEADERSHIP, SERVANT LEADERSHIP, DAN AUTHENTIC LEADERSHIP DALAM PERSPEKTIF ETIS - Agustini Srimulyani, Veronika (Widya Warta, 2021)
This research was a literature study that aimed to review the results of scientific research on several approaches to leadership and its development by providing comparisons of transformational leadership, servant leadership, and authentic leadership with ethical leadership. This research showed that the top management of the organization to adopt and demonstrate ethical leadership behavior, because it specifically focused on the moral and ethical aspects of leadership behavior, while the transformational, servant, and authentic leaders did not specifically focus on the ethical aspect. It was possible because it depended on the moral values of these leaders. For further leadership research, it is recommended to conduct ethical leadership research.